Aktywność enzymatyczna gleb leśnych w strefie oddziaływania Zakładów Azotowych "Puławy" S.A. = Enzymatic activity of forest soils in the zone of influence of Zakłady Azotowe "Puławy" S.A. - Bielińska, Elżbieta Jolanta; Domżał, Henryk (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The enzymatic activity of soils was tested in the zone of influence of Zakłady Azotowe "Puławy" S.A. [Nitric Works], in a deforested area ad-jacent to the Works and in forest areas of the Puławy Forest Inspectorate. At the same time, tests of the activity of dehydrogenases, phosphatases, urease and protease were carried out. The activity of dehydrogenases, phosphatases and protease in the examined soils varied within a broad range, however, they were clearly dependent on the anthropogenic pres-sure intensity. Such a regularity was not observed in case of urease activity. Direct positive correlations were indicated between the examined enzymes' activity and the content of mineral forms of nitrogen in soils. This proves that the ecosystem under examination is able to introduce nitrogen compounds of atmospheric origin into the biological cycle.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); gleby leśne; aktywność enzymatyczna; zanieczyszczenia przemysłowe; forest soils; enzymatic activity; industrial pollution